Penerapan Metode Drill dalam Meningkatkan Motivasi Belajar Pendidikan Pancasila terhadap Siswa Kelas IV SDN 09 Mattekko Palopo - HP, Hasnah (LP. Ma'arif Janggan Magetan, 2022)
This study generally aims to determine the extent to which the Drill method is applied in increasing motivation to study Pancasila Education in Class IV SDN 44 Rampoang. The type of research used in this study was classroom action research (Classroom Action Research) with the nature of PTK being carried out independently, which means that research is conducting CAR without collaboration with other teachers. In this case the researcher is directly involved in planning actions, taking actions, observing, reflecting, and others. Data analysis techniques in this study used descriptive qualitative analysis techniques. This classroom action research was carried out in a participatory and reflective manner, where the implementation process was carried out in a cyclical manner. After the writer discusses, conducts research, analyzes the results of the research, the results of the effect of applying the Drill method on increasing learning motivation are said to be successful because it can be seen and observed at every meeting there is an increase in each cycle. Based on data analysis, it was found that the success rate of students in one class was 42.85%, that is, out of 21 test takers, 9 people passed. Meanwhile, 12 people failed or 57.14%, because the test score was less than 70 and below the passing standard. so that it can be concluded that the Application of the Drill Method in Improving the Learning Motivation of Pancasila Education in Grade IV Students at SDN 44 Rampoang